Investigating the Important Criteria for Attraction of Private Section in Construction, Equipping and Operation of Hospitals using Public - Private Partnership Model(A review study) - alireza arab; Armin Monirabbasi; bagher dastyar (Tehran University of Medical Sciences, 2016)
Background: Partnership between public and private section is the cooperation between institutions in these sectors which perform to attain common goals and eliminate the limitations. This study aimed at investigating the important criteria for attraction of private section in health sector. Material and Methods: Based on studies and sample surveys, governments have essential role for codification of health policies and special programs in any country. In recent years, the costs of delivered health services increased exponentially and governments are looking for alternative mechanisms for cost reduction; meanwhile, the increased capacity in social programs is accompanied with considerable investments in infrastructures. This article investigated the utilization of different models by previous literature assessment in public- private partnership field and determined key and substantial criteria for these projectschr('39') success /failure. Although, the experience of their implementation is still very limited in our country and there is no accurate assessment based on case studies. Results: Based on study results, some criteria like possibility of returning part of participation costs in tendering for tender, goals and responsibilitychr('39')s clarity, fair and correct mutual risk attocation , lower public costs through less incumbency, private section motivation, clear mechanism monitoring ,conflict resolution and supporting policies from private investment have essential role for successful public- private partnership which special attention should  be drawn. Conclusion: Governments can have a suitable partnership with private sector in order to prevent increasing costs in rebuilding, maintenance and operation of public facilities like hospitals, considering budget limitations in public sector, providing innovation through opportunism in private section and more efficient risk management.